2022
DOI: 10.5312/wjo.v13.i3.267
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of intertrochanteric fracture fixation using proximal femoral nail with and without distal interlocking screws

Abstract: BACKGROUND Intertrochanteric (IT) fracture is one of the most common fractures seen in an orthopaedic practice. Proximal femoral nailing (PFN) is a common modality of fixing IT femur fracture. We retrospectively studied whether a PFN with two proximal lag screws can be done without distal interlocking screws in the 31-A1 and 31-A2 fracture patterns according to the Arbeitsgemeinschaft für Osteosynthesefragen/Orthopaedic Trauma Association (AO/OTA) guidelines for IT femur fractures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In a prospective comparative randomized study by Lil NA et al, the average fracture healing time was 8.8± 2.2 weeks in the locking group and (8.5±2.4 weeks) was in the unlocking group. There was no significant difference in the results 3 . Xing Li et al found the healing time as 14-16 weeks for patients having fracture pattern AO/OTA 31-A1 both in distal locked and unlocked patients 7 .…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…In a prospective comparative randomized study by Lil NA et al, the average fracture healing time was 8.8± 2.2 weeks in the locking group and (8.5±2.4 weeks) was in the unlocking group. There was no significant difference in the results 3 . Xing Li et al found the healing time as 14-16 weeks for patients having fracture pattern AO/OTA 31-A1 both in distal locked and unlocked patients 7 .…”
Section: Discussionmentioning
confidence: 69%
“…There are various complication occurrence rates in previous studies. Even so, it is seen that the results are not compatible with each other 3,15,18,19 . We did not have nail or locking screw breakage and the other results were similar to the previous studies.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations